Neurological Soft Signs and Post-Traumatic Stress Disorder: A Biomarker of Severity? - Belrose, Célia; Duffaud, Anais; Rakotoarison, Elsa; Faget, Catherine; Raynaud, Philippe; Dutheil, Frédéric; Boyer, Léa; Billaud, Jean-Baptiste; Trousselard, Marion (Frontiers in Psychiatry, 2020)
Background: The psychophysiological changes for individual suffering from chronic Posttraumatic Stress Disorder (PTSD) raise to the questions of how facilitate recovery and return to work. Negative alterations in neuro-cognition remain a complaint for patients and participate to long-term functional impairments. Neurological Soft signs (NSSs) appear as a candidate for better understanding these complaints. They have been reported in several mental disorders. They are found in several behavioral and/or neurocognitive disorders and are taken into account by psychiatric rehabilitation programs to support recovery. As few studies evaluate NSSs in PTSD, our study aims to assess NSSs in chronic PTSD and their relationships with PTSD severity. Method: 22 patients with a clinical diagnosis of chronic PTSD were evaluated in terms of PTSD severity (post-traumatic checklist scale, PCL5), NSSs (NSSs psychomotor skills scale, PASS), and well-being upon arrival to the hospital. Statistical non parametric analyses assessed the relationships between these variables. Results: NSSs were associated with severity in PTSD, namely with both a high level of negative alterations in cognition and mood, and an impairment in well-being. Females exhibited a high level of NSSs and PTSD severity. No impact of age was found. Three groups were identified based on the severity of the PTSD. Severe PTSD exhibited NSSs characterized by motor integration alterations. Conclusions: The severity of the PTSD was associated with NSSs. This proof of concept highlights the need for further research for better evaluating the clinical neuro-functional impairment. This will be helping for defining neurological remediation for promoting PTSD recovery.